Ravnikovi glasbenoestetski nazori v kontekstu dveh kompozicijskih šol - Bogunović Hočevar, Katarina (De musica disserenda, 2010)
In the 1930s, Janko Ravnik fell into creative silence. At the same time, two compositional schools took shape in Slovenia: that of Slavko Osterc and that of Lucijan Marija Škerjanc. The article establishes whether Ravnikar's silence came about as a consequence of the (non-)acceptance of Osterc's aesthetics and compositional ideas.
Keywords: Ravnik, Janko, 1891-1982; Glasbena estetika; Osterc, Slavko, 1895-1941; Škerjanc, Lucijan Marija, 1900-1973; slovenska glasba; 20.st.; Slovenia; Slovenija